Epidural administration of ketamine or fentanyl with bupivacaine for postoperative analgesia A comparative study - Al Maruf, Abdullah; Chowdhury, Iqbal Hosain; Lateef, Kazi Ashkar; Laskar, Manzoorul Haq; Kamal, Md Mustafa (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
The purpose of the study was to compare the analgesic effectiveness of epidural administration of ketamine mixed bupivacaine with fentanyl mixed bupivacaine in the management of postoperative pain. This prospective study was carried out in CMH, Bogra in one calendar year from July 2004 to June 2005. For postoperative pain management 100 patients of both sex, age ranging between 20 to 50 years, ASA physical status I and II scheduled for lower abdominal, pelvic and inguinal surgery were included in the study. All patients were divided into two groups. Epidural catheter was inserted in each patient through space between L3 to L2. Surgery was done under epidural anaesthesia in both groups. In group A (n=50) surgery was done with 0.5% bupivacaine and fentanyl (bupivacaine 1.5 ml/segment + fentanyl 2?g/ml). In group B (n=50) surgery was done with 0.5% bupivacaine and ketamine (bupivacaine 1.5ml/segment + ketamine 0.3mg/kg body weight). Epidural analgesia was continued in postoperative ward with 6 ml 0.25% bupivacaine + fentanyl 2?g/ml in group A and with 6 ml 0.25% bupivacaine + ketamine 0.3mg/kg bodyweight in group B, 4 hourly for 24 hours. The efficacy of analgesia was assessed by using Visual Analogue Scale (VAS) and Verbal Rating Scale (VRS). Mean VAS and mean VRS were less than 3 in both groups, which proved adequate postoperative analgesia. Differences of mean VAS and mean VRS between two groups were statistically not significant. Haemodynamic parameters, respiration and oxygenation were within normal range in both groups. Postoperative complications, like inadequate analgesia, post operative nausea and vomiting (PONV), headache and vertigo were less in both groups. It was observed that epidural administration of both bupivacaine mixed with ketamine and bupivacaine mixed with fentanyl found safe, effective and tolerable for postoperative pain management. DOI: http://dx.doi.org/10.3329/jbsa.v22i1.18097 Journal of BSA, 2009; 22(1): 21-25